Determining technological parameters for obtaining ta15 titanium alloy blanks with improved mechanical characteristics using the electron-beam 3D printing method - Akhonin, S.; Nesterenkov, V.; Pashynskyi, V.; Matviichuk, V.; Motrunich, S.; Berezos, V.; Klochkov, І.; Пашинський, В. В. (ПП "ТЕХНОЛОГІЧНИЙ ЦЕНТР"; Український державний університет залізничного транспорту, 2024)
The object of this study is the process of electron beam 3D printing of articles made of TA15 titanium alloy powder. Peculiarities of the structure and properties formation of alloy blanks, obtained by this method have been described. Influence of process parameters (electron beam power and geometric scanning parameters) on the characteristics of the material were considered.  Step of displacement of the beam trajectory changed from 0.1 to 0.25 mm with an interval of 0.05 mm. Specific energy of the electron beam varied from 20 to 70 J/mm3 for every trajectory displacement step.  The macrostructure was examined visually while the microstructure was studied by optical microscopy. Mechanical properties were determined by uniaxial tension and impact bending tests. It was established that depending on the 3D printing parameters the macrostructure of most samples is dense but with unfavorable parameters non-fusions or shrinkage porosity defects may form. The microstructure of the dendritic type has an α´+β lamellar-acicular morphology, its dispersity and shape of  α´–phase areas vary depending on the process parameters.  A scanning step of 0.2 mm and a beam energy of 40 J/mm3 allows obtaining a dispersed microstructure in which there are no non-fusions and shrinkage micropores. The value of the Rm is 27 %, and the R0.2 is 24 % higher than that of the alloy obtained by the conventional technology of electron beam melting. The A5 is 3.2 times higher. However, impact toughness of the sample with dendrite unfavorable orientation to the direction of load applying may be lower compared to conventional technology. The results could be used for devising commercial technology of high strength titanium alloys parts produced by 3D printing.
Keywords: electron beam 3D printing; titanium alloy; TA15; technological parameters; metallographic studies